3D RVE Models Able to Capture and Quantify the Dispersion, Agglomeration, and Orientation State of CNT in CNT/PP Nanocomposites - Bhuiyan, Md A.; Pucha, Raghuram V.; Kalaitzidou, Kyriaki (Frontiers in Materials, 2016)
The focus of this study is to investigate the capabilities of 3D RVE models in predicting the tensile modulus of carbon nanotube polypropylene (CNT/PP) composites which differ slightly in the dispersion, agglomeration and orientation states of CNT within the PP matrix. The composites are made using melt mixing followed by either injection molding or melt spinning of fibers. The dispersion, agglomeration and orientation of CNT within the PP are experimentally altered by using a surfactant and by forcing the molten material to flow through a narrow orifice (melt spinning) that promotes alignment of CNT along the flow/drawing direction. An elaborate image analysis technique is used to quantify the CNT characteristics in terms of probability distribution functions (PDF). The PDF are then introduced to the 3D RVE models which also account for the CNT-PP interfacial interactions. It is concluded that the 3D RVE models can accurately distinguish among the different cases (dispersion, distribution, geometry and alignment of CNT) as the predicted tensile modulus is in good agreement with the experimentally determined one.